Effect of sugar cane molasses and tofu waste on the inhibitory activity of cell free fermentation broth of streptomyces antibioticus K-6 - Astrid Aulia Hamida; Noor Erma Nasution; Isnaeni Isnaeni (Pharmaciana, 2019)
The use of waste as source of nutrition for human, animals, plants, and microorganism has been reported. The aim of this study was to observe the influence of sugar cane molasses (SCM) and tofu waste (TW) in various concentrations on the inhibitory effect of cell free fermentation broth (CFFB) of Streptomyces antibioticus K-6 isolated from plantation  soil compare  to International Streptomyces Project (ISP) standard  media. The fermentation was performed in 150 rpm rotary shaker at 37ºC for five days. The  inhibitory activity was  investigated using diffusion agar on the nutrient agar media to determine ratio of  SCM and TW by which the largest growth inhibitory zone achieved. Escherichia coli ATCC 25922 was used as a test microorganism. 10% of Streptomyces antibioticus K-6 starter was inoculated into nine compositions  of  SCM, TW and its combination containing media. The result indicated that SCM and TWmight be used as the component of fermentation medium of Streptomyces antibioticus K-6 for producing active metabolites. The activity of  CFFB was exhibited as a diameter of growth  inhibitory  zone  against the  test  bacteria; in which the largest value (24.4 mm) was detected in the combination of 0.5% SCM and 0.5% TW containig medium after  two days  incubation.